Water solubility of copper sulphate from polymers - Guiné, Raquel (2003)
To study the solubility of the copper sulphate in water, different types of tablets were prepared from different polymers with different percentages of CuSO4. The tablets were left in water for some days and the amount of CuSO4 released from the tablets was determined by measuring the absorbency of the final solution. In the first phase of this work 10 samples were prepared, corresponding to two similar sets. The results from these two sets were not much different, and similar samples registered approximately the same amount of CuSO4 in the water. By the seventh day more than the maximum amount of CuSO4 expected was already registered in the solution, meaning that all the copper sulphate present had been transferred from the tablets to the water. To try to get some more information about the influence of various factors on the solubility of the CuSO4, another experiment was carried out and more tablets of different sizes and from different polymers were prepared. From the results obtained it was possible to take some conclusions regarding the way both factors, thickness and type of polymer, influence the release of the copper sulphate from the tablets.